2019
DOI: 10.1117/1.nph.6.4.045005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic responses in preterm-born neonates to visual stimulation: classification according to subgroups and analysis of frontotemporal–occipital functional connectivity

Abstract: How neurovascular coupling develops in preterm-born neonates has been largely neglected in scientific research. We measured visually evoked (flicker light) hemodynamic responses (HRs) in preterm-born neonates (n ¼ 25, gestational age: 31.71 AE 3.37 weeks, postnatal age: 25.48 AE 23.94 days) at the visual cortex (VC) and left frontotemporal lobe (FTL) using functional near-infrared spectroscopy (fNIRS) neuroimaging. We found that the HR characteristics show a large intersubject variability but could be classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 93 publications
(122 reference statements)
1
13
0
Order By: Relevance
“…In line with a previous study that found large intersubject variability in hemodynamic responses in neonates (39), we grouped the participants into one of three subgroups. Subgrouping was based on the median hemodynamic responses obtained during walking in Andago.…”
Section: Responder Analysis and Subgroupsmentioning
confidence: 99%
“…In line with a previous study that found large intersubject variability in hemodynamic responses in neonates (39), we grouped the participants into one of three subgroups. Subgrouping was based on the median hemodynamic responses obtained during walking in Andago.…”
Section: Responder Analysis and Subgroupsmentioning
confidence: 99%
“…The physiological reasons underlying these differences are likely multi-factorial, but grounded in the substantial developmental changes in brain development and neurovascular coupling in infancy ( Roche-Labarbe et al, 2012 ). The morphology of preterm newborns’ HRF correlates significantly with the weight and height at birth, rather than with postmenstrual age ( Karen et al, 2019 ), thus showing individual differences even within the same age group.…”
Section: Introductionmentioning
confidence: 95%
“…Over the past years, fNIRS was proven to be a valuable technique to study brain activity in humans of all ages, from preterm-born neonates (e.g., Karen et al. 4 ) to elderly, 5 , 6 in freely moving subjects in naturalistic environments, 7 in several subjects in parallel (hyperscanning), 8 , 9 as part of computer interfaces, 10 and in combination with electroencephalography (EEG), 11 fMRI, 12 , 13 magnetoencephalography (MEG) (e.g., Huppert et al. 14 ), positron emission tomography (PET) (e.g., Rostrup et al.…”
Section: Neuroimaging With Fnirs: How To Correctly Interpret the Signalsmentioning
confidence: 99%